Developmental Aspects of Glucose and Calcium Availability on the Persistence of Memory Function Over the Lifespan - Holahan, Matthew R.; Tzakis, Niko; Oliveira, Fernando A. (Frontiers in Aging Neuroscience, 2019)
An important aspect concerning the underlying nature of memory function is an understanding of how memories are acquired and lost. The stability, and ultimate demise, of memory over the lifespan of an organism remains a critical topic in determining the neurobiological mechanisms that mediate memory representations. This has important implications for the elucidation and treatment of neurodegenerative diseases such as Alzheimer’s disease (AD). One important question in the context of preserving functional plasticity over the lifespan is the determination of the neurobiological structural and functional changes that contribute to the formation of memory during the juvenile time frame that might provide protection against later memory dysfunction by promoting the establishment of redundant neural pathways. The main question being, if memory formation during the juvenile period does strengthen and preserve memory stability over the lifespan, what are the neurobiological structural or functional substrates that mediate this effect? One neural attribute whose function may be altered with early life experience and provide a mechanism to preserve memory through the lifespan is glucose transport-linked calcium (Ca2+) buffering. Because peak increases in glucose utilization overlap with a timeframe during which spatial training can enhance later memory processing, it might be the case that learning-associated changes in glucose utilization would provide an important neural functional change to preserve memory function throughout the lifespan. The glucose transporters are proteins that are reduced in AD pathology and there is evidence that glucose reductions can impair Ca2+ buffering. In the absence of an appropriate supply of ATP, provided via glucose transport and glycolysis, Ca2+ levels can rise leading to neural vulnerability with ensuing pathological outcomes. In this review, we explore the hypothesis that enhancing glucose utilization with spatial training during the preadolescent period will provide a functional enhancement that regulates glucose-dependent Ca2+ signaling during aging or neurodegeneration and provide essential neural resources to preserve functional plasticity and memory function.